Batyrs as a marker of the cultural landscape: a philosophical analysis - Orazbayeva, D.Ye. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
In the reviving process of history and culture of modern Kazakhstan, it is becoming increasingly common to install monuments to heroes who have become a symbol of statehood and patriotism. The establishment of monuments and memorials is one of the tools for the development of national identity. The research of mon-uments to heroes, understanding and interpretation of their essence and meaning allows to comprehend the contemporary Kazakh worldview and philosophy. The article provides a philosophical analysis of the practic-es of regional memorialization of local heroes (batyrs). The research includes case analyses of Kazakh batyrs as Zholan Toleu-uly, Ketbuqa batyr, Tolek batyr, Yerden Sansyzbay-uly, Yeset Koki-uly, Dauymshar batyr, Zhidebay batyr and Derbisaly Aidabol-uly. The results of field research conducted in the South Kazakhstan, Karaganda, Aktobe and Ulytau regions allowed to study the location of monuments and the features of their memorialization. The research methodology used visual analysis and interviews with local residents to collect information about memorable events. The article applied field research and interviews with local residents. The description of monuments in the cultural landscape of the regions presented in the article concludes that the local heroes of the pre-Soviet period contribute the development of national identity and patriotism in modern Kazakhstan. The authors compiled a register of local monuments to batyrs established by descendants and native authorities that complements the historical picture and allows for a more comprehensive under-standing of the processes of memorialization of batyrs in the regions of the country.
Батырлар мәдени ландшафтың маркері ретінде: философиялық талдау
Батыры как маркер культурного ландшафта: философский анализ
Keywords: batyr; memorial; monument; memory activism; shezhire; cultural landscape